Using fungal–bacterial community analysis to explore potential microbiomes to manage Meloidogyne incongnita - Qipeng Jiang; Yong Wang; Jiamin Yu; Jinfeng Wang; Shiping Guo; Dongyang Liu; Xiangwen Yu; Lianqiang Jiang; Gang Long; Daojiang Xi; Shuhong Chen; Yue Wang; et al. (Frontiers in Microbiology)
Rhizosphere microbial communities strongly affect outbreaks of root-knot nematode (RKN) disease. However, little is known about the interactions among fungi, bacteria and RKN. The bacterial and fungal community compositions in the rhizospheres of four representative tobacco varieties, both resistant and susceptible to RKN, were characterized using 16S rRNA gene sequencing for bacteria and internal transcribed spacer gene sequencing for fungi. Our findings revealed that the fungi played crucial roles in facilitating the cross-kingdom and symbiotic fungal–bacterial interactions to suppress RKN. Moreover, our investigation suggested Microbacterium as a potential microbial antagonist against RKN based on its enhanced presence in RKN-resistant tobacco genotypes, and the relative abundance of Microbacterium was 34.49% greater in the rhizosphere of resistant tobacco than that of susceptible tobacco significantly. Notably, the richness of fungal community enhanced tobacco’s microbe-associated resistance to RKN through the positive regulation of the richness and diversity of bacterial community and the relative abundance of Microbacterium. This study underscores the critical role of the fungus–dominated fungal–bacterial community in bolstering tobacco resistance against RKN. The potential antagonistic role of Microbacterium presents promising avenues for innovative RKN management strategies.